Biological in-vivo measurement of dose distribution in patients' lymphocytes by gamma-H2AX immunofluorescence staining: 3D conformal- vs. step-and-shoot IMRT of the prostate gland - Zwicker, Felix; Swartman, Benedict; Sterzing, Florian; Major, Gerald; Weber, Klaus-Josef; Huber, Peter E.; Thieke, Christian; Debus, Jürgen; Herfarth, Klaus (Radiation oncology, 2011)
Background: Different radiation-techniques in treating local staged prostate cancer differ in their dose- distribution. Physical phantom measurements indicate that for 3D, less healthy tissue is exposed to a relatively higher dose compared to SSIMRT. The purpose is to substantiate a dose distribution in lymphocytes in-vivo and to discuss the possibility of comparing it to the physical model of total body dose distribution. - Methods: For each technique (3D and SSIMRT), blood was taken from 20 patients before and 10 min after their first fraction of radiotherapy. The isolated leukocytes were fixed 2 hours after radiation. DNA double-strand breaks (DSB) in lymphocytes' nuclei were stained immunocytochemically using the gamma-H2AX protein. Gamma-H2AX foci inside each nucleus were counted in 300 irradiated as well as 50 non-irradiated lymphocytes per patient. In addition, lymphocytes of 5 volunteer subjects were irradiated externally at different doses and processed under same conditions as the patients' lymphocytes in order to generate a calibration-line. This calibration-line assigns dose-value to mean number of gamma-H2AX foci/ nucleus. So the dose distributions in patients' lymphocytes were determined regarding to the gamma-H2AX foci distribution. With this information a cumulative dose-lymphocyte-histogram (DLH) was generated. Visualized distribution of gamma-H2AX foci, correspondingly dose per nucleus, was compared to the technical dose-volume-histogram (DVH), related to the whole body-volume. - Results: Measured in-vivo (DLH) and according to the physical treatment-planning (DVH), more lymphocytes resulted with low-dose exposure (< 20% of the applied dose) and significantly fewer lymphocytes with middle-dose exposure (30%-60%) during Step-and-Shoot-IMRT, compared to conventional 3D conformal radiotherapy. The high-dose exposure (> 80%) was equal in both radiation techniques. The mean number of gamma-H2AX foci per lymphocyte was 0.49 (3D) and 0.47 (SSIMRT) without significant difference. - Conclusions: In-vivo measurement of the dose distribution within patients' lymphocytes can be performed by detecting gamma-H2AX foci. In case of 3D and SSIMRT, the results of this method correlate with the physical calculated total body dose-distribution, but cannot be interpreted unrestrictedly due to the blood circulation. One possible application of the present method could be in radiation-protection for in-vivo dose estimation after accidental exposure to radiation.
Gesehen am 30.01.2023